2023
DOI: 10.3390/su151411120
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Simulator: An Agent-Based Framework with Human Behavior Modeling for Pandemic-Impact Assessment to Build Sustainable Communities

Abstract: It is crucial to immediately curb the spread of a disease once an outbreak is identified in a pandemic. An agent-based simulator will enable policymakers to evaluate the effectiveness of different hypothetical strategies and policies with a higher level of granularity. This will allow them to identify vulnerabilities and asses the threat level more effectively, which in turn can be used to build resilience within the community against a pandemic. This study proposes a PanDemic SIMulator (PDSIM), which is capab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Another approach for epidemics modeling focuses on the use of ABMS. Many researchers have worked to explain the emergent epidemic behavior of simple interactions within a community [26,[36][37][38][39][40][41]. According to Miksch et al [26], a significant benefit of agent-based epidemic modeling is that it allows exceptional flexibility to design very elaborate epidemic processes.…”
Section: Abms In Epidemic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach for epidemics modeling focuses on the use of ABMS. Many researchers have worked to explain the emergent epidemic behavior of simple interactions within a community [26,[36][37][38][39][40][41]. According to Miksch et al [26], a significant benefit of agent-based epidemic modeling is that it allows exceptional flexibility to design very elaborate epidemic processes.…”
Section: Abms In Epidemic Modelingmentioning
confidence: 99%
“…Additionally, Crooks and Hailegiorgis [37] performed a set of experiments to determine the effects of geographical interactions and concluded that geospatial setups truly determine the outcomes of an epidemic. Another example is Weligampola et al [41], where the authors introduce the Pandemic Disease Simulation (PDSIM) framework, an innovative ABMS that addresses the impact of the COVID-19 pandemic on diverse communities. PDSIM incorporates attributes like gender, age, ethnicity, and other individual characteristics to assess the susceptibility of different community groups to the COVID-19 pandemic.…”
Section: Abms In Epidemic Modelingmentioning
confidence: 99%
“…Another approach for epidemics modeling focuses on the use of Agent-based modeling and simulation. Many researchers have worked with agent-based models to explain the emergent epidemic behavior of simple interactions within a community [33,[43][44][45][46][47][48]. According to Miksch et al [33], a significant benefit of agent-based epidemic modeling is that it allows exceptional flexibility to design very elaborate epidemic processes.…”
Section: Abms In Epidemic Modelingmentioning
confidence: 99%
“…Additionally, Crooks and Hailegiorgis [44] performed a set of experiments to determine the effects of geographical interactions and concluded that geospatial setups truly determine the outcomes of an epidemic. Another example is Weligampola et al [48], where the authors introduce the Pandemic Disease Simulation (PDSIM) framework, an innovative agent-based model that addresses the impact of the COVID-19 pandemic on diverse communities. PDSIM incorporates attributes like gender, age, ethnicity, and other individual characteristics to assess the susceptibility of different community groups to the COVID-19 pandemic.…”
Section: Abms In Epidemic Modelingmentioning
confidence: 99%